2007
DOI: 10.1358/mf.2007.29.7.1074689
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of ketamine, nimodipine, gabapentin and imipramine in partial sciatic nerve transection model of neuropathic pain in rat: An experimental study

Abstract: The aim of this research is to study the effects of nimodipine, gabapentin, ketamine and imipramine in the partial sciatic nerve transection (PST) model of neuropathic pain in rats. PST was produced in young Wistar rats of either sex by partial destruction of the sciatic nerve. A decrease in the latency to paw withdrawal reaction on the hot plate was considered as development of neuropathy. The drugs were given daily from the third day of the procedure, and evaluation was done on days 7, 14, 21 and 28. There w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 0 publications
1
14
0
Order By: Relevance
“…Both clinical and animal studies have shown that ketamine can be applied for treating many kinds of chronic pain, such as neuropathic pain, cancer pain, and complex regional pain syndrome [4,5,37] . The present results show that a low dose of ketamine (30 g/kg) administration did not affect the pain threshold of the neuropathic rats, while 100 g/kg ketamine showed obvious effects on mechanical allodynia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both clinical and animal studies have shown that ketamine can be applied for treating many kinds of chronic pain, such as neuropathic pain, cancer pain, and complex regional pain syndrome [4,5,37] . The present results show that a low dose of ketamine (30 g/kg) administration did not affect the pain threshold of the neuropathic rats, while 100 g/kg ketamine showed obvious effects on mechanical allodynia.…”
Section: Discussionmentioning
confidence: 99%
“…tors, nicotinic receptors, voltage-gated ion channels, and the gamma-aminobutyric acid (GABA) receptor are all involved in the analgesia of ketamine [2,3,[5][6][7][8][9] . Very interestingly, some other studies have suggested that glia are also involved in opioid receptor, NMDA receptor, serotonergic receptor, and GABA receptor function [10][11][12][13] .…”
mentioning
confidence: 99%
“…Although imipramine given daily at 3 mg/kg needed 21 days to modulate hyperalgesia in the partial sciatic nerve transaction model of neuropathy [15] , we have observed that a single subcutaneous injection of imipramine could be enough to relieve allodynia in rats for a relatively prolonged time (70 min when administering 0.5 mg).…”
Section: Discussionmentioning
confidence: 78%
“…Amitriptyline suppressed mechanical allodynia following peripheral administration, but not following intraperitoneal injection, in a rat model of neuropathic pain [14] . Hota et al [15] reported that imipramine modulated hyperalgesia and allodynia in a partial sciatic nerve transaction model of neuropathic pain. No clear data on the effect of doxepin administered alone in animal models of allodynia are available.…”
Section: Introductionmentioning
confidence: 99%
“…98,99 Tricyclic antidepressants (imiprimine and reuptake inhibitors [paroxetine and milnacipran]) reduce both thermal and mechanical hyperalgesia. 86,100 Amitriptyline is also effective as a post-treatment against thermal hyperalgesia. 101 …”
Section: Partial Sciatic Ligationmentioning
confidence: 99%